Strategic Trade Cost Allocation and Internal Pricing Autonomy: A Literature Review on Multinational Tax Avoidance through Transfer Pricing - Ruslaini; Yessica Amelia (International Journal of Management, Accounting & Finance (KBIJMAF), 2026)
This qualitative literature review explores how multinational enterprises (MNEs) utilize strategic trade cost allocation and internal pricing autonomy to engage in tax avoidance through transfer pricing. Drawing on recent academic studies, the review synthesizes insights on how firms manipulate Incoterms, delegate pricing rights, and align managerial incentives to shift profits across jurisdictions. It highlights the dual role of transfer pricing as both a tax planning instrument and a corporate governance challenge. The review also examines the interaction between tax regulations—such as the OECD’s BEPS framework—and managerial decision-making authority within MNEs. By comparing findings across multiple empirical and theoretical studies, this paper provides a comprehensive understanding of the mechanisms and limitations of current transfer pricing practices. The results emphasize the need for stronger alignment between regulatory enforcement, internal control structures, and global transparency standards.